Numerical and experimental study on the heat transfer properties of the composite paraffin/expanded graphite phase change material. (May 2015) - Luo, Jian-Feng; Yin, Hong-Wei; Li, Wen-Yu; Xu, Zhong-Jie; Shao, Zheng-Zheng; Xu, Xiao-Jun; Chang, Sheng-Li
Abstract: The composite phase change materials (PCMs) can be obtained by heating and compressing the mixture of squama expanded graphite (EG) and paraffin, and they have high anisotropic thermal conductivity. The phase-change heat transfer properties of the composite paraffin/EG PCMs are studied numerically and experimentally. In the numerical simulation, the phase change heat transfer model is simplified as a one-dimensional monolayer, and the monolayer is heated by two stable heat fluxes at both sides. In the experiment, the PCM composite is placed in a metal box, and the underside of the metal box is heated by an electric stove. A heat flow is found to be transferred from the side wall of the metal box to the cover board, and then the composite PCMs are heated by the cover board. This experimental phenomenon is validated by the numerical simulation. The experimental results show that the anisotropic property of the thermal conductivity of the composite PCM is very obvious, and the temperature curves are deflexed and scattered during the apparent heat transfer process of the PCMs of liquid state. The numerical results prove that the above phenomena of deflexed and scattered temperature curves are caused by the convection between the environment fluid and the aluminum cover board. The correctness of the both experimental method and numerical method is validated with each other.